BLOOD AND SEMINAL PLASMA MINERAL PROFILE OF BUFFALO BULLS IN RELATION TO FERTILITY - MAVI, P S; SIDHU, S S; BAHGA, C S; KUMAR, RAVI; SINGH, NARINDER; SINGH, PRAHLAD (The Indian Journal of Animal Reproduction, 2010)
Eleven healthy Murrah buffalo bulls were divided into two groups on the basis of their fertility i.e.low fertile and high fertile (conception rate< 30% and >30%). The average conception rate In low andhigh fertile groups was 24.1 and 34.02, respectively. Blood serum and seminal plasma were analyzedfor various micro elements. Blood serum zinc, manganese and iron were higher by 5.63, 10.17 and14.11 percent in high fertile than low fertile group. Similarly seminal plasma zinc, manganese and ironwere higher by 10.31, 2.71 and 10.47 percentin high fertile compared to low fertile group. Blood serumand seminal copper was lower by 8.99 and 7 .14 per cent in high fertile from low fertile group respectively.Concentration of copper and manganese In blood serum and seminal plasma showed significantdifferences (P
Keywords: Mineral profile; Buffalo bulls; Fertility